Global marketing and advertising understanding cultural paradoxes - Mooij, Marieke K. de 1943- (SAGE, 1997)
Global Marketing and Advertising describes the characteristics of a global brand, how advertising adds value to brands, the concept of culture and culture's consequences for values and motivation in advertising, and how culture influences perception of advertising. Marieke de Mooij's application of Geert Hofstede's 5-D model to marketing and advertising is an essential theme of this book.